Prospects for Regulating a Dog Meat Consumption Ban in Indonesia: A Comparative Study with Taiwan - Raisya Syafira Zahra; Kayus Kayowuah Loweleba (PDIH Untag Semarang, 2025)
The rapid development of the pet industry in Indonesia has been accompanied by an increase in unethical dog trade practices, ranging from exploitation in breeding to cruelty in distribution and slaughter. This study aims to examine how the form and substance of regulations prohibiting the consumption of dog meat based on the Taiwan Animal Protection Act (TAP) are implemented in Taiwan and how they can be applied in Indonesia. The normative legal method used in this study is an approach comparing Indonesian and Taiwanese regulations. The results of this study show that the TAP explicitly prohibits the consumption, sale, and killing of dogs. They also impose heavy criminal and administrative sanctions and enforcement mechanisms used by animal protection inspectors and local government agencies. In contrast, law enforcement in Indonesia relies on Article 302 of the Criminal Code and Law Number 18 of 2009 concerning Animal Husbandry and Health because there is no clear law regulating the consumption of dog meat. Therefore, Indonesia needs to implement special regulations such as TAP or laws to close legal loopholes and improve animal welfare protection, especially for protection against the sale of dog meat consumption.